ANALISIS PROGRAM KEGIATAN SEKOLAH DALAM PENGEMBANGAN KECERDASAN SPIRITUAL SISWA DI MTS SA AN-NUR CISEENG BOGOR - Yani, Ahmad; Indra, Hasbi; Rahman, Imas Kania (Tawazun: Jurnal Pendidikan Islam, 2019)
One thing that is important to live this life, namely by developing spiritual intelligence, so that we can live this life based on religious value This study aims to determine the development of spiritual intelligence by taking the background of Madrasah Tsanawiyah SA An-Nur Ciseeng - Bogor. The focus of the problem to be studied is: 1) madrasah program in developing students’ spiritual intelligence in MTs SA An-Nur Ciseeng - Bogor. 2) What are the supporting and inhibiting factors in developing students’ spiritual intelligence in MTs SA An-Nur Ciseeng - Bogor. This research is a qualitative research. Research carried out with the preparation, implementation, completion. Research subject is teacher role. Data collection techniques used observation, interview, and documentation. This analysis is done by giving meaning to the data collected, and from that meaning the researchers draw conclusions. From the results of the research, it is known that the programs in MTs SA An-Nur Ciseeng - Bogor in developing spiritual intelligence include: the development of consistency attitude (istiqomah), humility (tawadu’), endeavor and surrender (tawakkal), sincerity and perfection (ihsan). That is with the way teachers continue to provide motivation to learners, teachers also familiarize students to morals and always get used to worship in madrasah like dhuha prayer together. Keywords : spiritual quotient, the development of spiritual intelligence, morals